Incomplete Knowledge, Rumour and Truth Seeking: When conspiracy theories become news. (3rd July 2017) - Konkes, Claire; Lester, Libby
Abstract : Conspiracy theories can no longer be consigned to the fringes of media; they are a feature of news and journalism and can be defined as attempts to find causal explanations for events in covert plots rather than more prosaic processes. Often a pejorative label, journalists know that conspiracies can be sites for significant news-making. This empirical study explores the conditions and practices that lead to conspiracy theories entering news narratives. It focuses on the intense news coverage of a child sexual crime in Hobart, Tasmania that became a conspiracy theory involving the highest levels of government and the judiciary. It examines how Hobart's Mercury newspaper sourced its stories and finds that the conspiracy theory gained traction when official statements were deemed unsatisfactory and journalists sought other perspectives which enabled critics, including the newspaper, to attack the Tasmanian Government.